Features of Complicity of the Crime - Čimburović, Goran; Igrački, Jasmina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
In this paper, the author analyses the institute of complicity. Complicity is one of the most complex institute criminal justice, which is determined in accordance with certain principles of the state, the criminal policy and tasks of criminal legislation. This dangerous form of crime, which implies the participation of several persons in committing a criminal offence, in modern criminal law is given more attention. Complicity emerged relatively late as a criminal justice institute. The systematic legal and law definition of the institute of complicity began only in the eighteenth century, when the criminal law developed as a separate branch of legislation. In the earlier legislation, there were no particular provisions regarding complicity, but there was a concealment of criminal acts with the offence, but not the concurrence of several persons during the commission of the same crime. It is this reason, the absence of boundaries between assistance and concurrence of a person during the same criminal offence, that led to all perpetrators of criminal offences being punished equally.